Prognostic value of two geriatric screening tools in a cohort of older patients with early stage Non-Small Cell Lung Cancer treated with hypofractionated stereotactic radiotherapy. Issue 3 (April 2020) - Cuccia, Francesco; Mortellaro, Gianluca; Mazzola, Rosario; Donofrio, Alessandra; Valenti, Vito; Tripoli, Antonella; Matranga, Domenica; Lo Casto, Antonio; Failla, Giuseppe; Di Miceli, Giuseppe; Ferrera, Giuseppe
Abstract: Objectives: To investigate whether assessment with two geriatric screening tools shows a correlation with clinical outcomes of patients aged 65 years or more, with early-stage Non-Small Cell Lung Cancer (es-NSCLC) treated with hypofractionated stereotactic radiotherapy. Methods: From March 2014 to June 2018 we retrospectively evaluated 42 patients with stage I and II lung tumors. Patients were assessed with Charlson Comorbidity Index (CCI) and G8 screening tool. Median age was 74 years (range, 65–91). Stereotactic radiotherapy was performed with Helical Tomotherapy delivering 50–70 Gray (Gy) in 8–10 fractions. Toxicity was evaluated using Common Terminology Criteria for Adverse Events v4.0 criteria. Results: Median CCI and G8 scores were 6 (4–11) and 14 (12–17), respectively. With a median follow-up of 14 months (3–37), we observed: 3 cases of acute Grade 2 (G2) radiation pneumonitis, 1 late G2 non-cardiac chest pain, 1 late G2 dysphagia and 1 case of late G2 radiation pneumonitis. At statistical analysis, G8 scores ≤14 were significantly associated with late toxicity rates ( p = .0073). Local failure was predictive of disease free survival and Overall Survival ( p < .001 and p = .001). Death occurred in 12 patients, 6 for non-cancer related causes, with 1- and 2-yrs cancer specific survival rates of 94.8% and 90%, 1- and 2-yrs OS rates of 93% and 80%, respectively. Conclusions: Our experience shows a correlation between G8 scores and late toxicity in older patients treated with stereotactic radiotherapy for lung cancer, suggesting the need for prospective studies evaluating its use for the identification of patients at higher risk of adverse events.